Eliza in the uncanny valley : anthropomorphizing consumer robots increases their perceived warmth but decreases liking - Kim, Seo Young (2021)
Consumer robots are predicted to be employed in a variety of customer-facing situations. As these robots are designed to look and behave like humans, consumers attribute human traits to them—a phenomenon known as the “Eliza Effect.” In four experiments, we show that the anthropomorphism of a consumer robot increases psychological warmth but decreases attitudes, due to uncanniness. Competence judgments are much less affected and not subject to a decrease in attitudes. The current research contributes to research on artificial intelligence, anthropomorphism, and the uncanny valley phenomenon. We suggest to managers that they need to make sure that the appearances and behaviors of robots are not too human-like to avoid negative attitudes toward robots. Moreover, managers and researchers should collaborate to determine the optimal level of anthropomorphism.